HUBUNGAN TINGKAT PENGETAHUAN, SIKAP, DAN PERILAKU CUCI TANGAN PAKAI SABUN (CTPS) DENGAN KEJADIAN DIARE PADA SISWA SEKOLAH DASAR NEGERI - Suci Amalia (Jurnal Ilmu Kesehatan Immanuel, 2026)
Diarrhea remains a public health problem among elementary school-aged children. Handwashing with soap, as part of a Clean and Healthy Lifestyle (PHBS), plays a crucial role in preventing infectious diseases such as diarrhea. Students' knowledge and attitudes toward handwashing with soap are key factors influencing hand hygiene behavior. This study used a Systematic Literature Review (SLR) approach with the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) method to identify, select, and synthesize scientific evidence related to the relationship between knowledge, attitudes, and handwashing with soap behavior and diarrhea among public elementary school students. A literature search was conducted using Google Scholar, Semantic Scholar, PubMed, SINTA, and Scopus using the keywords "knowledge," "attitude," "handwashing with soap behavior," "handwashing with soap," "diarrhea," and "elementary school students" for publications published in 2021–2026. Of the 30 identified articles, 14 met the inclusion criteria and were further analyzed. The synthesis results demonstrate consistent findings that good knowledge and attitudes are significantly associated with more optimal handwashing with soap practices and a reduced incidence of diarrhea in elementary school students. Keywords: Knowledge, Attitude, Behavior, Handwashing with Soap, Diarrhea, Elementary School, PRISMA, SLR.